Encapsulation Methods and Releasing Mechanisms of Encapsulated Active Drug - N’GUESSAN-GNAMAN, Kakwokpo Clémence; TUO-KOUASSI, Nakognon Awa; DALLY, Ismael; AKA-ANY-GRAH, Sandrine; CHOUGOUO KENGNE-NKUITCHOU, Rosine Désirée; LIA, Arthur José; ANIN, Apo Laurette; N’GUESSAN, Alain (Journal of Drug Delivery and Therapeutics, 2024)
Substances of plant origin are chemically unstable and easily oxidized by external conditions. However, they have to remain in their bioactive form when they are used in food, pharmaceutical, nutraceutical and cosmetic industries. Encapsulation method is an effective technique that should protect them preventing the degradation of these active substances and thus prevent them from losing their activities. In this review, the strategies for encapsulating plant substances and their preparation methods including emulsification, atomization, coaxial electrospray system, lyophilization, coacervation, in situ polymerization, melt extrusion, supercritical fluid technology, fluidized bed coating etc. were discussed. The release mechanisms of plant active substances were also presented. The choice of an appropriate encapsulation technique and wall material depends on the final use of the product and the processing conditions involved. The use of liposomes, ethosomes, phytosomes, emulsions, microspheres, microcapsules, solid lipid nanoparticles including formulations based on plant substances has enhanced their therapeutic effects. With the use of all these encapsulation systems, the formulation is delivered in a targeted manner, giving it an on-site effect, and the bioavailability of the formulation is also improved. With these new drug delivery systems, actives and extracts used in herbal formulations exhibit improved stability, sustained release from the formulation, protection against toxicity, and improved therapeutic efficacy. Keywords : nanoparticles, bioactive substance, formulation